Circular synthetic aperture radar systems for on-the-ground object detection - Mohammad Poor, Mojtaba (2012)
Detecting on-the-ground object is a subject of interest for some applications. An example of application is detection of airport‟s runway Foreign Object Debris (FOD), which is an important issue in the aviation safety. In this way, radar imaging has several inherent advantages over other techniques, including larger coverage area, robustness in bad weather conditions, and ability to operate unabated for twenty-four hours. Currently existing FOD-detection systems are using very high carrier frequencies at millimetre-wave, and are prone to be affected by different weather conditions. Moreover, their usage is limited to free-space applications due to their inability in penetrating into solid materials. Furthermore, two radar technologies are possible to be investigated for such applications, namely Synthetic Aperture Radar (SAR) and bistatic radar. SAR concept is applicable in this regard with some modification, especially in terms of movement trajectory. In this thesis, a circular monostatic and a circular bistatic system of low-carrier frequency synthetic aperture radar are proposed which can be used for such applications. In both proposed systems, wideband Linear Frequency Modulated (LFM) pulses are generated and employed. The advantages of using LFMs include their higher signal-to-noise ratio and lower hardware complexity. Both proposed systems were analyzed theoretically, modelled and verified through field experiments. Two new processing algorithms for each of the systems were also developed to be used in the system. The ability of the proposed circular monostatic system is shown through detecting one or more metallic cylinders as small as 1cm diameter and 1.5~2.5 cm height at 7-10 m ranges and different angles. The output of the system is a radar image of the area where the position of the objects is highlighted in it. Similar action is repeated for the bistatic proposed system by detecting cylinders as small as 2 cm diameter and 2.5 cm height at 5-7 m ranges. The ability of the system is verified because the system produces a radar image of the area by highlighted points at the position of the objects.